ROLE OF ECONOMY IN SMALL BUSINESS DEVELOPMENT - Turaeva Z. T. (Galaxy International Interdisciplinary Research Journal, 2022)
Small business is the foundation and component of a competitive market economy. Small business is the most popular, dynamic and flexible form of entrepreneurship in our country. The process of digitization as the basis of the digital economy is determined by the requirements of objective reality and relies primarily on the use of digital technologies in the activities of its subjects. Digital technologies are changing the way organizations are organized. Digital news and technology serve as part of the solution. Known as the “Fourth Industrial Revolution” (Industry 4.0), Blockchain envisages the introduction of digital technologies such as the Internet of Things, artificial intelligence into several fast-changing economic sectors, thereby transforming an entire economy into a digital economy. At present, digitalization has covered all business entities.